A new original conception in rock magnetism, paleomagnetism and geomagnetism: An origin of the reversed magnetization of rocks on Earth - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2018)
So far the field-reversal theory has been accepted to account for the reversed remanent magnetization (RM) of rocks on the Earth. Orlický (2014) revealed a frequent occurrence of the antiferromagnetic (AFM) Fe-Ti oxides in the rocks. Now I have renamed these minerals as the Fe-Ti ferrimagnetic-antiferromagnetic chemical phases (Fe-Ti FriM-AFM ChPs). They may have either cubic spinel, or tetragonal spinel symmetry, respectively. They behave as the Fe-Ti polycrystalline materials. These Fe-Ti FriMAFM ChPs are the two sublattice A and B ChPs, with some specific magnetic behaviour. The titanomagnetite (Ti-Mt, Curie temperature, TC = 230 °C; FriM alignment) and the titanomaghemite (Ti-Mgh, N´eel temperature, TN = 450 °C; AFM alignment) containing rocks have been identified as the representants of the the Fe-Ti FriM-AFM cubic spinel ChPs. The interactions with the magnetizing field, with the Weis molecular fields (Weiss-Heisenberg forces) have generated the reversally oriented internal field. The reversally oriented spontaneous magnetization has arosen in the rock. This internal field has been identified as the most important phenomenon leading to the production of the reversally oriented magnetization in the Fe-Ti FriM-AFM ChPs containing rocks. The equations expressing the magnetic behaviour of the magnetic susceptibility (κ) of rocks versus temperature have been derived. The Fe-Ti FriM-AFM cubic spinel can undergone the transition in favour of the Fe-Ti FriM-AFM tetragonal spinel in the rocks, due to a change of the thermodynamic conditions in nature. The reversed RM has supposed been inparted from the Fe-Ti FriM-AFM cubic spinel during this alteration-transition processess. Such tetragonal spinel is more stable and it is able to survive in the rocks innature. The results of laboratory magnetization of the selected groupings of rocks have been presented below.